Intracranial hypertension in Kenyan children with cerebral malaria - Newton, Charles R J C (Department of Paediatrics and Child Health, 2018)
Cerebral malaria is a common encephalopathy in African children, but the cause of death and neurological sequelae are unknown. This dissertation examines the hypothesis that raised intracranial pressure (ICP) is a determinant of poor outcome in Kenyan children with cerebral malaria. The opening cerebrospinal fluid pressure was raised in all 26 children in whom it was measured on admission and 92% of 35 children in whom it was measured after admission. Brain stem signs, particularly an abnormal respiratory pattern, absent pupillary responses and a lack of spontaneous eye movement were associated with a death. In 33 children who died with cerebral malaria, at least 18-42% had clinical features of transtentorial herniation, according to the criteria used. Intracranial pressure monitoring was performed in 18 children with severe CM, of whom 14 had computerised tomography (CT) and in 10 the basal cranial arteries were monitored with transcranial Doppler (TCD) sonography. Three children with severe intracranial hypertension (maximum ICP > 60 mmHg and minimum cerebral perfusion pressure (CPP) < 40 mmHg) had a poor outcome despite aggressive therapy with mannitol. One child with a maximum ICP of 151 mmHg died with the signs of uncal and medullary stages of herniation. In the other 2 children, middle cerebral artery velocity and vascular resistance monitored with TCD sonography changed with ICP and CPP. Both of these children had diffuse brain swelling associated with generalised hypodensity on their acute CT scans. These children survived° with cerebral atrophy on their convalescent scans and severe neurological deficits. In the 8 children with intermediate intracranial hypertension (maximum ICP 20-60 mmHg and CPP < 50 mmHg) mannitol was effective in controlling the intracranial hypertension. TCD was not reliable in detecting changes in ICP or CPP. Two of these children had acute brain swelling, but the tomographic density was normal and the swelling had resolved when the repeat scans were performed 12-24 days later. All the children with intermediate intracranial hypertension survived without major neurological sequelae. In the remaining 7 children who had ICP monitoring, the maximum ICP was <20 mmHg and mannitol was not administered. None of the CT scans showed brain swelling and the children survived without severe sequelae. In a further 9 children with severe malaria (6 with CM) the agonal stages were monitored with TCD. Three children with CM had sonographic features of progressive intracranial hypertension associated with signs of herniation, whilst the other children (including 3 with CM) did not have these sonographic features, although one had evidence of brainstem compromise before dying. Thus raised ICP is a feature of CM in Kenyan children. Severe intracranial hypertension is associated with a poor outcome and could be responsible for at least a third of the children dying from CM. Mannitol reduces the ICP, but does not prevent nor control severe intracranial hypertension.